Rearranging the pixel using Log-Cumulant Parameter Estimator and Healing of Restoration Technique (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Using second-kind statistics technique noise reduction is not mile stone in the field of image processing, the log-cumulant estimator is proposed for pixel parameter estimation of the log-normal distribution in medical image. The estimates of the shape parameter and scale parameter are independent for the log-cumulant estimator for noise reduction. Parameter estimation results from Monte Carlo simulation demonstrate that, the log-cumulant estimator is insensitive to noise samples and it leads to better performance noise reduction when compared to the moment estimator using Laplacian function.